2019
DOI: 10.3982/qe926
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian inference on structural impulse response functions

Abstract: I propose to estimate structural impulse responses from macroeconomic time series by doing Bayesian inference on the Structural Vector Moving Average representation of the data. This approach has two advantages over Structural Vector Autoregressions. First, it imposes prior information directly on the impulse responses in a flexible and transparent manner. Second, it can handle noninvertible impulse response functions, which are often encountered in applications. Rapid simulation of the posterior distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 75 publications
(101 reference statements)
0
19
0
Order By: Relevance
“…One approach is to assume that the shocks are independent and non‐Gaussian, and to exploit higher order moment restrictions to identify the causal structure (Lanne and Saikkonen, ; Gospodinov and Ng, ; Gouriéroux et al ., ). A second approach is to use a priori informative priors (Plagborg‐Møller, ). Here, we have shown that there is a third approach, which is to use an external instrument.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One approach is to assume that the shocks are independent and non‐Gaussian, and to exploit higher order moment restrictions to identify the causal structure (Lanne and Saikkonen, ; Gospodinov and Ng, ; Gouriéroux et al ., ). A second approach is to use a priori informative priors (Plagborg‐Møller, ). Here, we have shown that there is a third approach, which is to use an external instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Beaudry et al . () and Plagborg‐Møller () provide numerical evidence that in many cases the non‐invertible (non‐fundamental) representation of a time series may be very close to its invertible representation. With this motivation, we focus on non‐invertible IRFs that represent small departures from an invertible null.…”
Section: A Test Of Invertibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to what is done in the (Structural) VAR literature to compute confidence intervals for impulse response functions, one can quantify the uncertainty around the Wold components by, for example, bootstrapping the data using the estimated VAR parameters and the fitted residuals. Alternatively, one could conduct inference directly on the moving average representation of the data (without estimation and inversion of the VAR) along the line of Barnichon and Matthes () and Plagborg‐Moller (). We view this as an interesting avenue for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Macroeconomists now consider various types of news shocks, beginning with TFP news (Beaudry and Portier (2006)), and including government spending news (Ramey (2011)) and monetary policy news (Campbell, Evans, Fisher, and Justiniano (2012)). Plagborg‐Møller (2019) estimated point‐identified IRFs with news shocks directly using a prior on shapes. We use ranking restrictions to condition on shocks that lead to a TFP build‐up for TFP news shocks (the first shock) and mean‐reversion for TFP surprises: trueright leftλ×ra1,TFP0>ra1,TFP1>λ×ra1,TFP2with λ=1,λ×ra2,TFP0>ra2,TFP1>λ×ra2,TFP2with λ=1. These restrictions rule out aliasing of news and surprise shocks.…”
Section: Modelmentioning
confidence: 99%